Microbial Community Composition and Volatile Flavor Substances in Fermented Grass Carp with Rice Wine Lees during Fermentation and Correlation between Them - DUAN Zirui, YANG Xu, CHEN Xiao’e, GUO Quanyou (Shipin Kexue, 2025)
In order to understand the microbial community composition and the evolution of volatile flavor substances during the fermentation process of grass carp with rice wine less and to explore the possibility of using rice wine mash instead of rice wine lees for the fermentation of grass carp, high-throughput sequencing technology was used for sequencing and phylogenetic analysis of the bacterial and fungal communities in unfermented grass carp and three groups of air-dried fermented grass carp (made with lees fermented for 5 days, lees fermented for 2 days and mash fermented for 2 days, respectively), and gas chromatography-ion mobility spectrometry (GC-IMS) was used to analyze their volatile flavor substances. The results showed that the contents of moisture, alcohol and amino acid nitrogen increased with fermentation time, and the pH decreased. The mash fermentation group had the best performance in smell, color, taste and texture, with good overall acceptability. The dominant bacterial genera were Weissella, Citrobacter and Aeromonas in the early stage of fermentation. In the middle and late stages, the abundance of Pediococcus and Lactococcu increased, while the abundance of Citrobacter and Aeromonas decreased significantly. For all three fermented samples, the dominant fungal genus Pichia had an absolute advantage during the fermentation process. A total of 37 volatile flavor substances were detected in all samples, among which acetic acid ethyl ester, ethyl propanoate and 2-butanone, 3-hydroxy were the characteristic flavor substances of fermented grass carp with lees. Weissella, Lactococcu, Pichia and Saccharomyces cerevisiae had a significantly positive correlation with the production of various aroma substances. This study provides the basis for the screening of dominant strains and the optimization of the fermentation process of fermented grass carp.